THE THE ROLE OF LITERATURE IN ELT - Novasyari, Ressy; Novianty, Melisa; Intani, Dhaniella Putri (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2024)
Learning English is lifelong process and it needs the perfect strategies or techniques to keep learning it the whole life. One of the best ways is to introduce them to any kinds of literature. This strategy should be introduced as young as possible because it will become their habitual which will help them to understand English fully. It means that English as a language for communication contains many aspects that should be introduced, like culture, habits, social, etc. Teaching English through literature will build a bridge between English and its soul which will facilitate the students to learn and create a closer interaction with the target language and its complex soul.. Therefore this paper will explore what is Literature, kinds of literature and why teachers can use it as a powerful resource in teaching English